2019
DOI: 10.1016/j.chest.2018.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Noncommunicable Diseases

Abstract: Although air pollution is well known to be harmful to the lung and airways, it can also damage most other organ systems of the body. It is estimated that about 500,000 lung cancer deaths and 1.6 million COPD deaths can be attributed to air pollution, but air pollution may also account for 19% of all cardiovascular deaths and 21% of all stroke deaths. Air pollution has been linked to other malignancies, such as bladder cancer and childhood leukemia. Lung development in childhood is stymied with exposure to air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
184
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 581 publications
(256 citation statements)
references
References 113 publications
0
184
0
13
Order By: Relevance
“…Air pollution concentration in Australia is generally low relative to these standards, as the Australian population-weighted average PM 2.5 concentration for 2013 was estimated to be 5.93 μg m −3 (Brauer et al 2016), and no exceedances of hourly or annual air quality standards for NO 2 have occurred since the 1990s (SoE 2016). However, these guidelines do not reflect current research which has found no safe concentration levels of these pollutants (Kelly and Fussell 2016, Hanigan et al 2019, Schraufnagel et al 2019b.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Air pollution concentration in Australia is generally low relative to these standards, as the Australian population-weighted average PM 2.5 concentration for 2013 was estimated to be 5.93 μg m −3 (Brauer et al 2016), and no exceedances of hourly or annual air quality standards for NO 2 have occurred since the 1990s (SoE 2016). However, these guidelines do not reflect current research which has found no safe concentration levels of these pollutants (Kelly and Fussell 2016, Hanigan et al 2019, Schraufnagel et al 2019b.…”
Section: Introductionmentioning
confidence: 87%
“…The pollutants PM 2.5 and NO 2 are associated with a range of health effects including respiratory and cardiovascular diseases, and in extreme cases, mortality (Brugge et al 2007, Rückerl et al 2011, Hamra et al 2015, Kelly and Fussell 2016, Khreis et al 2017, Schraufnagel et al 2019a, 2019b. The associations between negative health effects and the concentration of pollutants are significant for acute and chronic exposure, although the exact associations vary between exposures (Rohr and Wyzga 2012, Hoek et al 2013, Atkinson et al 2014, Faustini et al 2014, Wyzga and Rohr 2015, Li et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can aggravate the symptoms of a child with asthma and threaten his/her life. Moreover, there is limited but increasing evidence that air pollution can affect children's lives by inducing diabetes and neurological development impairments [23]. Therefore, the range of ambient air pollution-related adverse effects is expanding, which can potentially shift its position upward among the human health risk factors.…”
Section: Air Pollution Health and The Economymentioning
confidence: 99%
“…*shangran.xie@mpl.mpg.de Efficient monitoring of airborne particulate matter (PM), especially particles with aerodynamic diameter less than 2.5 μm (PM2.5), is crucial for improving public health 1,2 . Reliable information on the concentration, size distribution and chemical characteristics of PMs is key to evaluating air pollution and identifying its sources 3 . Standard methods for PM2.5 characterization require sample collection from the atmosphere and post-analysis using sophisticated equipment in a laboratory environment, and are normally very time-consuming 4,5 .…”
mentioning
confidence: 99%
“…Environmental air pollution, caused by mixtures of solid and liquid microparticles, is of growing public concern for public health [10][11][12][13] . Particles of diameter less than 2.5 μm (PM2.5) are especially hazardous since they can penetrate deep into the respiratory system, causing severe damage [2][3][4] . A variety of non-optical techniques for monitoring PM2.5 particles have been developed in recent years, involving atmospheric sampling through impingement on an adhesive surface or filtering, followed by analysis using bulky and sophisticated equipment [14][15][16] .…”
mentioning
confidence: 99%